Pengaruh Model Pembelajaran STAD berbantuan Media Wordwall terhadap Kemampuan Berpikir Kritis Siswa Geografi SMA - Asmi, Nadiyah Annisa Tsabitul; Astutik, Sri; Pangastuti, Era Iswara; Mujib, Muhammad Asyroful; Nurdin, Elan Artono (Jurnal Pendidikan Geografi Undiksha, 2025)
Geography learning required methods, strategies, models, and media that were appropriate to help students better understand the material presented by the teacher. The purpose of this study was to examine the effect of the Student Teams Achievement Division (STAD) learning model assisted by Wordwall media on the critical thinking skills of high school geography students. This research was quantitative with a quasi-experimental design. The determination of the control and experimental classes was done using the homogeneity test with One Way Anova on SPSS version 26, followed by cluster random sampling using a lottery technique. The data collection techniques used were documentation, tests, and observation. The normality test using Kolmogorov-Smirnov proves to be normally distributed because the significance value for both the experimental class and the control class is 0.200. After the normality test is conducted, the Independent Sample T-Test is performed, which results in a Sig (2-tailed) value of 0.000. This means that the use of the STAD learning model assisted by Wordwall media significantly influences the critical thinking skills of high school geography students.